2007
DOI: 10.1002/jcb.21529
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and prostate cancer: An eclipsed truth in an androgen‐dominated scenario

Abstract: Prostate cancer is the commonest non-skin cancer in men. Incidence and mortality rates of this tumor vary strikingly throughout the world. Although several factors have been implicated to explain this remarkable variation, lifestyle and dietary factors may play a dominant role, with sex hormones behaving as intermediaries between exogenous factors and molecular targets in development and progression of prostate cancer. Human prostate cancer is generally considered a paradigm of androgen-dependent tumor; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 77 publications
(73 reference statements)
0
138
1
6
Order By: Relevance
“…25,26 Furthermore, accumulating evidence suggests that prostate carcinogenesis by alcohol is mediated through increased estrogens and decreased androgens and sex hormone-biding globulin. [27][28][29][30][31][32] Results regarding the effect of smoking on prostate cancer have been inconsistent. Our present results showed that smoking decreased the risk of prostate cancer in total subjects, but that this negative association might have been impaired in subjects whose cancer was detected by subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Furthermore, accumulating evidence suggests that prostate carcinogenesis by alcohol is mediated through increased estrogens and decreased androgens and sex hormone-biding globulin. [27][28][29][30][31][32] Results regarding the effect of smoking on prostate cancer have been inconsistent. Our present results showed that smoking decreased the risk of prostate cancer in total subjects, but that this negative association might have been impaired in subjects whose cancer was detected by subjective symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, presence of estrogens and insulin like growth factor (IGF-I) in milk has been hypothesized to be associated with risk of prostate cancer (Carruba, 2007;Weaver, 2009). But even five cups of milk/day would supply about only 1.3 mg calcium/day, which is too low to produce any significant impact on plasma estrogen concentration (Weaver, 2009).…”
Section: Vitamin D and Calciummentioning
confidence: 99%
“…Além disso, tem se associado a expressão local da aromatase e síntese de estrogênio ao crescimento de neoplasias benignas, como o leiomioma uterino e de neoplasias malignas como: câncer de endométrio, útero, próstata (Cunat et al, 2004;Cheng et al, 2006;Ishida et al, 2007;Czajica-Oraniec;Simpson, 2010) e da cavidade bucal (Cheng et al, 2006;Ishida et al, 2007) O estrogênio possui dois tipos de receptores, α e β (REα e REβ), codificados respectivamente por genes diferentes: ESR1 e ESR2, encontrados em locais cromossômicos diferentes (Bord et al, 2001;Carruba, 2007). Ambos apresentam alto grau de homologia no domínio de ligação de DNA, porém diferem consideravelmente no domínio N terminal e no domínio E. Essas diferenças sugerem que esses dois receptores apresentem funções distintas para as respostas biológicas e na regulação da transcrição gênica sob o comando do estradiol (Bardin et al, 2004).…”
Section: Hormônios: Androgênio E Estrogênio: Seus Receptores E a Enziunclassified
“…Ambos apresentam alto grau de homologia no domínio de ligação de DNA, porém diferem consideravelmente no domínio N terminal e no domínio E. Essas diferenças sugerem que esses dois receptores apresentem funções distintas para as respostas biológicas e na regulação da transcrição gênica sob o comando do estradiol (Bardin et al, 2004). O modo de ação de cada receptor depende da quantidade e do nível da expressão encontrada de cada um dele nos tecidos (Bord et al, 2001;Carruba, 2007).…”
Section: Hormônios: Androgênio E Estrogênio: Seus Receptores E a Enziunclassified
See 1 more Smart Citation